A Bcool survey of the magnetic fields of planet-hosting solar-type stars - Vidotto, Aline (My University, 2017)
We present a spectropolarimetric snapshot survey of solar-type planet hosting stars. In addition to 14 planet-hosting stars observed as part of the BCool magnetic snapshot survey, we obtained magnetic observations of a further 19 planet-hosting solar-type stars in order to see if the presence of close-in planets had an effect on the measured surface magnetic field (|Bℓ|). Our results indicate that the magnetic activity of this sample is congruent with that of the overall BCool sample. The effects of the planetary systems on the magnetic activity of the parent star, if any, are too subtle to detect compared to the intrinsic dispersion and correlations with rotation, age and stellar activity proxies in our sample. Four of the 19 newly observed stars, two of which are subgiants, have unambiguously detected magnetic fields and are future targets for Zeeman Doppler Mapping
PUBLISHED
Keywords: spectropolarimetric snapshot; spectropolarimetric snapshot